P014 Does separation of HIV and sexual health services affect the management of stis in people living with HIV?. (8th June 2017) - Colver, Helen; Ball, Rhiannon; Dhar, Jyoti
Abstract : Introduction: The presence of a bacterial STI increases the risk of HIV transmission. It is important that people living with HIV have easy access to STI treatment and that partner notification is robust. In our local area, HIV care is located and commissioned separately from the sexual health service. Does this affect STI treatment and partner notification? Methods: All HIV positive patients with a diagnosis of gonorrhoea, Chlamydia or new/infectious syphilis during 2015 were identified from laboratory results and computer records. Demographic details for each patient were recorded and the management of their STI assessed according to BASHH standards. Results: Discussion Barriers to timely treatment included difficulty contacting patients, need to travel to a different service to obtain medication and difficulty arranging appointments at acceptable times. Particular delays were noted in the management of syphilis. Clarification of each service's responsibilities with regard to contact tracing could improve partner notification rates. Even when HIV and sexual health services are not jointly commissioned, it is essential that both departments work together to develop robust pathways for the management of STIs identified in people living with HIV.